2012
DOI: 10.1590/s0102-695x2012005000064
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the photosynthetic conditions and pigment profiles of the colour strains of Hypnea musciformis from field-collected and in vitro cultured samples

Abstract: Abstract:Hypnea musciformis (Wulfen) JV Lamour. is a species of great economic interest as it produces κ-carrageenan and has shown biological activities against HIV and HSV viruses. This species displays different colour strains in its natural habitat, which may have implications for the biotechnological potential of the species. The aim of this study was to characterize the photosynthetic apparatus and pigment profile of three colour strains of H. musciformis (green, brown and red) in their natural habitat an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…The effective quantum yield of photosystem II (ΦPSII) was reduced by 50% in the waterlogged plants, compared to the control plants. Determination of ΦPSII has an advantage, since this variable is more sensitive to a large number of stressors than the Fv/Fm value, according to Fernandes et al (2012) since it has been found that the reduced plant health under prolonged soaking may result in biochemical alterations such as restriction of ribulose bisphosphate carboxylase (RuBPC), phosphoglycollate and glycollate oxidase activity, as well as severe damage to chloroplast membranes. These alterations restrict the electron transport chain during photosynthesis and negatively alter the efficiency of PSII (Ashraf, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The effective quantum yield of photosystem II (ΦPSII) was reduced by 50% in the waterlogged plants, compared to the control plants. Determination of ΦPSII has an advantage, since this variable is more sensitive to a large number of stressors than the Fv/Fm value, according to Fernandes et al (2012) since it has been found that the reduced plant health under prolonged soaking may result in biochemical alterations such as restriction of ribulose bisphosphate carboxylase (RuBPC), phosphoglycollate and glycollate oxidase activity, as well as severe damage to chloroplast membranes. These alterations restrict the electron transport chain during photosynthesis and negatively alter the efficiency of PSII (Ashraf, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Además de ser una de las reservas más importantes de nitrógeno en las algas (Martinez & Rico, 2006). Los resultados del presente estudio coinciden con los obtenidos en el trabajo realizado por Fernandes et al (2012), en Hypnea musciformes (Wulfen) J. V. Lamouroux, 1813, cuya concentración de ficoeritrina es predominante tanto en condiciones de cultivo como en condiciones naturales. En el estudio realizado por Costa et al (2001), los ejemplares de Gracilaria birdae de coloración roja, verdemarrón y verde, colectados en un mismo ambiente y posteriormente sometidos a un cultivo, se obtuvo que los ejemplares de mayor crecimiento fueron los de coloración roja.…”
Section: Discusión Y Conclusiónunclassified
“…have similar growth rates (although in different optimal light conditions). Martins et al (2009) and Fernandes et al (2012) also conducted studies related to two color variants, were they showed that both of those variants could be selected for aquaculture. The only taxonomic study using cultures of Hypnea species was held by .…”
Section: Possible Natural And/or Anthropogenic Explanations For the Pmentioning
confidence: 99%